The Effect of Discounts, Product Quality, and Display on Customer Buying Impluse (Case Study at Indomaret Store Sukodadi Branch) - Yahya Yahya; Nurul Badriyah; Titin Titin (Jurnal Price : Ekonomi dan Akuntasi, 2025)
This study aims to test the influence of partial, simultaneous and which variables are the most dominant influence between discounts ̧ product quality and display, on customer buying imoluse there is a significant relationship between the variables studied. The population in this study is customers of the Indomaret store Sukodadi branch with a simple random sampling technique. The sample in this study was 100 by distributing questionnaires. Then the data analysis method was taken using the Validity Test, Reliability Test, Multiple Linear Regression Analysis, Classical Assumption Test, Determination Coefficient, t-Test and F Test. The results of the study showed that from multiple linear regression analysis, the equation Y = 0.264 + 0.280 X1 + 0.268 X2 + 0.208 X3 was obtained. The results of the t-test (partial) were produced X1 = 4.574 > 1.984 and X2 = 4.135 > 1.984, X3 = 3.724 > 1.984 stated that the discount ̧ product quality and display both had a partial effect on impluse buying. Simultaneous tests were produced Fcal > Ftabel (51,600 > 2.70). It can be seen that the F test has a significant effect between discount (X1), product quality (X2), display (X3) simultaneously on the bound variable, namely impluse buying. From the results of this research, it can be concluded that the discount ̧ product quality and display can be seen from the calculation of the > t table. Meanwhile, discounts ̧ product quality and display simultaneously have a significant effect as seen from the results of F calculation > F table, and discounts have a more dominant influence on impluse buying.